Factors influencing the implementation of food sanitation hygiene in the canteen at Kendari Port - Pratama, Ichsan; Sarto; Daniel (Universitas Gadjah Mada, 2023)
Purpose: Food handlers still need to routinely wash their hands with hand soap or wear aprons/masks, as there are dirty outdoor areas and many flies in canteens at Kendari port. Previous studies found that education level, knowledge, attitude, training, and availability of facilities affect the implementation of food sanitation hygiene. However, there has yet to be research on the combination of these factors in influencing the implementation of food sanitation hygiene, and research on the application of food sanitation hygiene in port areas in Indonesia is still rare. The study aimed to identify one factor that must be present for the implementation of food sanitation hygiene that meets the requirements and does not meet the requirements and identify a combination of factors that influence the implementation of food sanitation hygiene. Methods: The study design was cross-sectional, and 16 canteens and 16 food handlers participated using total sampling techniques. Education level, knowledge, attitude, training, and availability of facilities were analyzed using Qualitative Comparative Analysis (QCA). Results: No single factor was mandatory for implementing food sanitation hygiene that meets or does not meet the requirements. QCA identified three pathways for implementing eligible and not-eligible food sanitation hygiene. Conclusion: Frequent or regular training and adequate facilities are essential to implement food sanitation hygiene that meets the requirements. Meanwhile, poor attitudes, never or rarely-received training, and inadequate facilities were essential factors that led to implementing food sanitation hygiene, which was needed to meet the requirements.